Advances in Biological Liquid Crystals. Issue 18 (20th March 2019) - Zhao, Jianguo; Gulan, Utku; Horie, Takafumi; Ohmura, Naoto; Han, Jun; Yang, Chao; Kong, Jie; Wang, Steven; Xu, Ben Bin
Abstract: Biological liquid crystals, a rich set of soft materials with rod‐like structures widely existing in nature, possess typical lyotropic liquid crystalline phase properties both in vitro (e.g., cellulose, peptides, and protein assemblies) and in vivo (e.g., cellular lipid membrane, packed DNA in bacteria, and aligned fibroblasts). Given the ability to undergo phase transition in response to various stimuli, numerous practices are exercised to spatially arrange biological liquid crystals. Here, a fundamental understanding of interactions between rod‐shaped biological building blocks and their orientational ordering across multiple length scales is addressed. Discussions are made with regard to the dependence of physical properties of nonmotile objects on the first‐order phase transition and the coexistence of multi‐phases in passive liquid crystalline systems. This work also focuses on how the applied physical stimuli drives the reorganization of constituent passive particles for a new steady‐state alignment. A number of recent progresses in the dynamics behaviors of active liquid crystals are presented, and particular attention is given to those self‐propelled animate elements, like the formation of motile topological defects, active turbulence, correlation of orientational ordering, and cellular functions. Finally, future implications and potential applications of the biological liquid crystalline materials are discussed. Abstract : A rich variety of biological soft materials, including inanimate and living matters, are rod‐shaped. They often undergo a striking liquid crystalline phase transition under various physicochemical conditions and external stimuli. Here, the complex interaction of components across multiple length scales, phase transition between distinct steady‐states, and dynamics that govern these processes are thoroughly discussed.